An Extension of Nobel's Multiplying Factor Method for Solutions of Dual and Triple q-Integral Equations (Contemporary Mathematics, 2024)
In this paper, we convert certain dual q-integral equations involving third Jackson q-Bessel functions to the first and second kind Fredholm q-integral equations by extending the multiplying-factor method introduced by Nobel. We also apply these results to convert a certain triple q-integral equations to two simultaneous Fredholm q-integral equations
Keywords: q-Bessel functions; dual q-integral equations; triple q-integral equations